Sistem Pendukung Keputusan Pengangkatan Guru Tetap Menerapkan Metode Weight Aggregated Sum Product Assesment (WASPAS) - Safrizal Barus; Vera Meikana Sitorus; Darmawan Napitupulu; Mesran Mesran; Supiyandi Supiyandi (STMIK Budi Darma, 2018)
Evaluation of honorary teachers is an activity that is generally high school or vocational. It is useful to know the results of teaching honorary teachers to their students. Assessment, evaluation and rewarding can be done to spur the performance of the teachers in teaching and learning process so as to improve teacher achievement, the assessment is done to obtain the honorable teachers who will be appointed as permanent teachers. In determining the order of permanent appointment of teachers, it often appears subjective from the decision-makers, so that there are problems and this causes the difficulty in determining prospective teachers. To determine the recommendation of the teacher can still be used the method of Weight Aggregated Sum Production Assessment (WASPAS). WASPAS method can be used to process the honorarium of honor teachers with the criteria that have been determined.